Investigating the possible role of LRP/LR in the pathogenesis of Parkinson’s Disease and cancer - Burns, Jessica (My University, 2021)
Currently, over 10 million people suffer from Parkinson’s disease (PD). α-synuclein and parkin are both implicated in PD, where mutations in α-synuclein result in its aggregation. However, the α-synuclein C-terminal domain (CTD) prevents this aggregation. Parkin, an E3 ubiquitin ligase, rescues cells from the effects of α-synuclein aggregation and in PD, mutations in parkin result in its loss-of-function. In addition, parkin has been suggested to be the link between PD and cancer. The 37kDa/67kDa Laminin Receptor Precursor/ high-affinity Laminin Receptor (LRP/LR)is a multifunctional receptor protein that plays a role in the pathogenesis of neurodegenerative disorders as well as cancer. This study aimed to determine the role of LRP/LR in PD and the effect that overexpressing LRP::FLAG has on colorectal cancer. To this end, human embryonic kidney (HEK293) cells and late-stage colorectal cancer cells (DLD-1) were stably transfected with pCIneo-LRP::FLAG and co-localization studies, western blot analysis, MTT cell viability and mitochondrial membrane potential assays were performed. In addition, co-localisation studies were done on neuroblastoma (SH-SY5Y)cells. The results show that LRP/LR and the human telomerase reverse transcriptase (hTERT) co-localise with the PD-related proteins -synuclein and parkin in SH-SY5Y cells. In addition, LRP/LR and -synuclein are shown to co-localise in HEK293 non-transfected and LRP::FLAG transfected cells. Furthermore, LRP::FLAG overexpression was shown to increase -synuclein CTD levels, cell viability and mitochondrial membrane potential in HEK293 cells. Interestingly, LRP::FLAG overexpression in DLD-1 cells decreased cell viability and mitochondrial membrane potential. LRP/LR was also shown to co-localise with parkin in DLD-1 non-transfected and LRP::FLAG transfected cells. However, hTERT and parkin were only found to co-localise in LRP::FLAG transfected cells. Finally, LRP::FLAG was shown to increase parkin levels in DLD-1 cells. In conclusion, this study shows that LRP/LR may play a protective role in PD and that LRP::FLAG overexpression could inhibit the progression of colorectal cancer. Therefore, therapeutic approaches aiming at increasing LRP/LR protein levels may represent a novel alternative for PD and cancer treatment
A dissertation submitted in fulfilment of the degree of Master of Science (MSc) in Biochemistry Cell Biology in the Faculty of Science, School of Molecular and Cell Biology, University of the Witwatersrand